Poliomyelitis. Issue 853 (November 1996) - Kidd, D.; Williams, A. J.; Howard, R. S.
Abstract : 1996 is polio awareness year. This paper reviews the clinical syndrome of acute paralytic poliomyelitis and its sequelae. We discuss epidemiological studies of the syndrome of late functional deterioration many years after the acute infection and the current hypotheses of the pathophysiology of such disorders. Recent evidence has suggested that potentially treatable factors may be implicated in the majority of such patients and it is therefore important to exclude such disorders before attributing late functional deterioration to progressive post-polio muscular atrophy.